2013
DOI: 10.4236/psych.2013.43a048
|View full text |Cite
|
Sign up to set email alerts
|

Anything but Race: Avoiding Racial Discourse to Avoid Hurting You or Me

Abstract: The present research examines how Whites employ strategic colorblindness-the strategic assertion that race should not and/or does not matter-in interracial interactions, and how stereotype threat and concern about non-Whites influence the use of this conversational technique. Because colorblindness can be egalitarian or anti-egalitarian (Knowles, Lowery, Hogan, & Chow, 2009), one must define colorblindness in order to understand how it is employed. Two studies provide evidence that both concerns that racial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…In the current experiments, we were interested in testing racial color blindness by comparing the use of racial labels when an interaction was interracial, and thus race was salient, to when race was assumed to not be salient for non‐Black participants, for example when the ACT depicted two White actors (Hegarty, ; Zarate & Sanders, ; Zarate & Eliot, ). It is important, however, to explore whether non‐Black participants do not mention race in a same‐race context with two Black actors and if not, whether the reason for avoiding race is because race is not salient, because they believe that using race is unfair to Blacks (Goff et al., ), or because they are trying to create the appearance that minorities do not differ from the White majority and that they are not prejudiced (Neville et al., ). It would also be important to investigate and compare how Black participants would respond to an intergroup interaction compared to two White actors interacting and two Black actors interacting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the current experiments, we were interested in testing racial color blindness by comparing the use of racial labels when an interaction was interracial, and thus race was salient, to when race was assumed to not be salient for non‐Black participants, for example when the ACT depicted two White actors (Hegarty, ; Zarate & Sanders, ; Zarate & Eliot, ). It is important, however, to explore whether non‐Black participants do not mention race in a same‐race context with two Black actors and if not, whether the reason for avoiding race is because race is not salient, because they believe that using race is unfair to Blacks (Goff et al., ), or because they are trying to create the appearance that minorities do not differ from the White majority and that they are not prejudiced (Neville et al., ). It would also be important to investigate and compare how Black participants would respond to an intergroup interaction compared to two White actors interacting and two Black actors interacting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research suggests that inducing concerns about being prejudiced can motivate greater endorsement of racial color blindness. For example, in an experiment by Goff, Jackson, Nicholas, and Di Leone (), participants completed a measure of racial prejudice, then were randomly assigned to receive false feedback that they were either high or low in negative attitudes toward Blacks. Results revealed that participants who were given high prejudice feedback scored higher on a subsequent strategic racial color blindness scale than those who were given low prejudiced feedback.…”
Section: Strategic Racial Color Blindnessmentioning
confidence: 99%
See 3 more Smart Citations